(untitled) (Journal of Medicine, 2023)
Impaired insulin secretion and resistance remain the core defects in T2DM, but at least six other pathophysiological abnormalities contribute to the dysregulation of glucose metabolism. Diabetic nephropathy is one of the most common microvascular complications and a major cause of end-stage renal disease. Despite many treatment options available, diabetic kidney disease continues to affect a large population with diabetes. The kidneys have the highest DPP-4 expression level in mammalians. DPP- 4 is expressed in several segments of the nephron and the tubule interstitium, placing it at the nexus of inflammation, immune system activation, glomerular and proximal tubular function, salt regulation, and kidney fibrosis. Moreover, DPP-4 expression and urinary activity are up-regulated in diabetic nephropathy, highlighting its role as a potential target to manage diabetic nephropathy. DPP-4 inhibition is associated with mitigation of diabetic and hypertensive renal injury and protection of renal function. Renal glucose reabsorption by SGLT proteins is a critical component of glycemic regulation. SGLT2 protein expression is increased in human diabetic nephropathy even with advanced kidney disease indicating that SGLT2 can be an effective target in treatment of diabetic nephropathy. This review article discusses roles played by DPP-4 inhibitors and SGLT-2 inhibitors alone and in combination in diabetic nephropathy supported by clinical evidences. MEDLINE and EMBASE were searched through September 2022. Randomized controlled trials published in English that evaluated SGLT2 inhibitors and/or DPP4 inhibitors in patients with T2DM were selected. J MEDICINE 2023; 24: 43-49